2000
DOI: 10.1002/(sici)1097-4644(20000801)78:2<334::aid-jcb15>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus type 16 E6 and HPV-16 E6/E7 sensitize human keratinocytes to apoptosis induced by chemotherapeutic agents: Roles of p53 and caspase activation

Abstract: We and others have previously reported that human papillomavirus (HPV)-16 E6 protein expression sensitizes certain cell types to apoptosis. To confirm that this sensitization occurred in HPV's natural host cells, and to explore the mechanism(s) of sensitization, we infected human keratinocytes (HKCs) with retroviruses containing HPV-6 E6, HPV-16 E6, HPV-16 E7, or HPV-16 E6/E7. Apoptosis was monitored by DNA fragmentation gel analysis and direct observation of nuclei in cells stained with DAPI. Exposure of HKCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…25), and the treatment of cervical cancer cell lines with chemotherapeutic compounds such as cisplatin often induces elevated levels of p53 even in the presence of the HPV E6 protein (11,29). It was therefore possible that DHA might be inducing apoptosis by increasing cellular p53 levels.…”
Section: Resultsmentioning
confidence: 99%
“…25), and the treatment of cervical cancer cell lines with chemotherapeutic compounds such as cisplatin often induces elevated levels of p53 even in the presence of the HPV E6 protein (11,29). It was therefore possible that DHA might be inducing apoptosis by increasing cellular p53 levels.…”
Section: Resultsmentioning
confidence: 99%
“…23 However, E6 can sensitize human keratinocytes to apoptosis induced by chemotherapeutic drugs. 24 The most physiological way, however, to trigger programmed cell death is the engagement of CD95 receptor to its ligand (CD95L). 25 This interaction can be mimicked by agonistic anti-CD95 (APO-1) antibodies.…”
Section: When Cervical Carcinoma Cells Were Monitored For Apoptotic Smentioning
confidence: 99%
“…Therefore any radiation damage would not be sufficiently repaired, and damaged cells would be more likely to die during mitosis as they progress through the cell cycle. E6 has previously been shown to sensitize mammary epithelial cells, fibroblasts and keratinocytes to chemically induced death (Xu, Meikrantz et al 1995, Hawkins, Demers et al 1996, Liu, McKalip et al 2000, Liu, Zhao et al 2007), but has been reported to have the opposite effect or no effect in other cell types exposed to ionizing radiation or DNA-damaging chemicals (DeWeese, Walsh et al 1997, Hampson, El Hady et al 2001, Shai, Nguyen et al 2007). Thus, the radiosensitizing effect might be specific to a few cell types, including keratinocytes, the natural hosts for HPVs, and be dependent on the E6*I isoform.…”
Section: Discussionmentioning
confidence: 99%